Implementasi Prinsip Moderasi Beragama dalam Pembelajaran PPKN pada Siswa Kelas X di SMAN 4 Blitar - Wisnu Fataaz Dzaki; Dwi Retnani Srinarwati; Riki Suliana (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Indonesia, as a country whose population adheres to various religions, faces a high risk of religious intolerance. As an effort to address conflicts rooted in religious intolerance, it is necessary to foster an attitude of religious moderation based on the principles of justice, balance, and tolerance. One way to implement the principles of religious moderation is through Civics education for students. The purpose of this research is to describe the implementation of the principles of religious moderation in Civic learning for Grade X students at SMAN 4 Blitar. The method used in this research is a descriptive qualitative method. Data collection techniques include interviews, observation, and documentation. The data analysis techniques employed are data reduction, data presentation, and conclusion drawing. The research findings show that the implementation of the principles of religious moderation in Civics learning for Grade X students at SMAN 4 Blitar is carried out throughout various learning processes. The principles of justice and balance are applied in student grouping activities as well as in the assessment stage. Meanwhile, discussion activities using the jigsaw learning method serve as the main activity in applying the principles of religious moderation in Civics learning at SMAN 4 Blitar.